Fluorescence turn-on of salicylaldimine ligands by co-ordination with magnesium and amines. (29th October 2018) - Gao, Zideng; Feng, Haojie; Wang, Shunyi; Huang, Yuanfang; Ren, Xueqin; Pang, Long; Hu, Shuwen
Abstract : A novel and easily available fluorescent chemosensor that showed highly selective recognition toward magnesium and amines in ethanol is established. Abstract : A new fluorescence enhancement mechanism based on Schiff base ligand and magnesium complexation is established. The co-ordination number of the Schiff base ligand–magnesium complex (2 : 1) can be tuned to 1 : 1 in the presence of amines to induce significant fluorescence enhancement. Using this approach, a novel and easily available fluorescent chemosensor was designed, which showed highly selective recognition toward magnesium and amines in ethanol.